ANOTASI PUTUSAN DISSENTING OPINION DALAM PUTUSAN KASASI - Taufik Maulani (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Abstract: Judges 'decisions in court are the core of the parties' agreement. Decision of the Supreme Court of the Republic of Indonesia Number: 579/K/AG/2010 concerning Settlement of Inheritance Disputes. Trying out this research is trying to explain, is there a legal basis for differences of opinion in the judicial decision in Indonesia. The juridical-normative method was used in analyzing this study. Primary and secondary data sources from the decision of the Supreme Court, Jurisprudence Books and Legislation Regulations are sources of data in completing this research. The results showed first, the legal basis for the difference of opinion in the court's decision in Indonesia; secondly, the legal basis / consideration of the cassation panel of judges who reject the cassation filed by the parties in the decision Number: 579/K/AG/2010 is an unacceptable lawsuit because the cassation applicants are not the heirs who are experts and heirs who are trying exist in KHI regulated in Presidential Instruction Number 1 of 1991; and three, the legal implications of differences of opinion that proved positive as the judges' hard efforts in compiling the normative legal grounds and considerations, description, basis, and legal liability to take a fair decision, including the decision of cassation Number: 579/K/AG/ 2010 who refused to give heir to the heirs decided that the gift really took effect before the birth of KHI in 1991.Abstrak: Putusan hakim di pengadilan merupakan inti penyelesaian sengketa bagi pihak-pihak yang berperkara. Penelitian ini berfokus pada perbedaan pendapat (dissenting opinion) dalam Putusan Kasasi Mahkamah Agung Republik Indonesia Nomor: 579/K/AG/2010 tentang Penyelesaian Sengketa Waris. Sehingga penelitian ini mencoba menjelaskan, apakah ada dasar hukum dissenting opinion dalam putusan pengadilan di Indonesia. Metode yuridis-normatif digunakan dalam menganalisis penelitian ini. Sumber data primer dan sekunder dari putusan Mahkamah Agung, Kitab-kitab Fikih dan Peraturan Perundang-undangan menjadi sumber data dalam melengkapi penelitian ini. Hasil penelitian menunjukkan pertama, dasar hukum kebolehan adanya dissenting opinion dalam putusan pengadilan di Indonesia; kedua, dasar/pertimbangan hukum majelis hakim kasasi yang menolak permohonan kasasi yang oleh para pihak dalam putusan Nomor: 579/K/AG/2010 adalah gugatan tidak dapat diterima karena para pihak pemohonan kasasi bukan para pihak ahli waris yang sebenarnya dan ahli waris pengganti baru ada dalam KHI yang diatur dalam Inpres Nomor 1 Tahun 1991; dan ketiga, implikasi hukum dari adanya dissenting opinion terbukti positif sebagai usaha keras para hakim dalam menyusun dasar dan pertimbangan hukum secara normatif, uraian, dasar, dan pertimbangan hukum untuk mengambil sebuah putusan yang adil, termasuk pula putusan kasasi Nomor: 579/K/AG/2010 yang menolak memberikan harta waris kepada ahli waris pengganti sudah benar karena ketentuan itu belaku sebelum lahirnya KHI Tahun 1991.